A shared vision of quality of life: Partnering in decision-making to understand families' realities. (February 2019) - Gorgos, Andreea; Ghosh, Shuvo; Payot, Antoine
Summary: Quality of life (QOL) measures are increasingly used when important prognostication and treatment decisions need to be made in the care of a critically ill child. Unfortunately, health-care professionals and families experience difficulties when attempting to accurately predict and estimate QOL for a patient. Aspects such as subjectivity, complexity and adaptation to illness play an important role in how QOL is ultimately experienced. This often leads to inaccurate estimates of QOL, when performed by individuals other than the patient, such as clinicians or family members. In order to make decisions in the best interest of the patient, a partnership between families and clinicians must be fostered, based on communication, trust and mutual understanding of values. This article will attempt to describe some of the challenges that come into play when assessing QOL for a patient and will provide tools for building a clinician–family partnership in the decision-making process.